Fostering narrative writing practices through the use of ICT tools and genre based instruction (2016)
ABSTRACT: This paper is an action research report that describes the effects of the implementation of genre based instruction and the use of information and communication technologies (ICT) such as Storybird with the purpose of fostering the narrative writing practices of eight graders in a public educational institution of Medellin. A teacher journal, two surveys and two students‟ writing tasks were the data collection methods applied during the project in order to determine the effectiveness of using genre based instruction and ICT in this EFL scenario. This study also shows how some actions were implemented to achieve the goal of promoting narrative writing practices. Finally, it presents the analysis of the data gathered to build up the findings, the conclusions and some reflections on them.